Impacts of the Wetland Environment on Demographic Development During the Neolithic in the Lower Yangtze Region—Based on Peat and Archaeological Dates - Shao, Konglan; Zhang, Jianping; He, Keyang; Wang, Can; Lu, Houyuan (Frontiers in Earth Science, 2021)
Wetlands were an important resource for the hunting-gathering and early farming communities in coastal areas in the Neolithic. However, the relationship between the development of the wetland environment and the human population remains unclear due to the lack of successive wetland environmental changes throughout the Holocene in coastal areas. Here, the summed probability distributions (SPD) of radiocarbon dates of peat were used as an indicator and combined with archaeological radiocarbon dates to reconstruct the wetland environmental and demographic changes during the Neolithic in the lower Yangtze region. The results showed that the shifts in demographic centers and population development related to wetland environment with peat formation. The first shift of the demographic center was from the hilly regions to the coastal plain and occurred during ca. 8,300-8,000 cal. yr BP, which might be caused by the attractiveness of survival resources offered by the coastal wetland environment and the 8.2 ka event. The second shift occurred from the Ningshao Plain to the Taihu region and might be attributed to the widespread waterlogged environment in the Ningshao Plain. The peak of demographic development coincided with the peak of peat formation during the middle Holocene in the lower Yangtze region, indicating that the wetland environment facilitated changes in human societies. The formation of peat might be related to the sea-level and El Niño-Southern Oscillation (ENSO) events, however, further studies are required for deep comprehension. The present study is an attempt at identifying the past impacts of the wetland environment on demographic development, and can form the basis for a more comprehensive understanding of the interactions between the humans and their living environment.